2017
DOI: 10.1002/mp.12362
|View full text |Cite
|
Sign up to set email alerts
|

Metallic nanoparticles irradiated by low‐energy protons for radiation therapy: Are there significant physical effects to enhance the dose delivery?

Abstract: Although effects from a physical standpoint are limited, the high linear energy transfer profile at the nanoparticle surface generates detrimental events in the cell, in particular ROS-induced damage and local heating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Similar theoretical studies performed using protons showed a negligible macroscopic physical enhancement [47][48][49][50]. Martinez-Rovira et al [50] performed simulations to evaluate the dose enhancement when protons pass through a medium containing GNPs.…”
Section: Physical Enhancementmentioning
confidence: 84%
See 1 more Smart Citation
“…Similar theoretical studies performed using protons showed a negligible macroscopic physical enhancement [47][48][49][50]. Martinez-Rovira et al [50] performed simulations to evaluate the dose enhancement when protons pass through a medium containing GNPs.…”
Section: Physical Enhancementmentioning
confidence: 84%
“…They did not report a significant energy deposition increase for a realistic configuration of the model. In another study, an energy-dependent emission of electrons from GNP surface was reported [48]. For a 5 nm GNP, they reported 8% and 20% increases in number of electrons ejected per incident proton after interaction with 1.3 and 4 MeV protons, respectively, compared to irradiation in the absence of GNPs.…”
Section: Physical Enhancementmentioning
confidence: 90%
“…Some more recent studies turn to other nanostructures called hydrogenated nanodiamonds (H-NDs) which has been proposed as radiosensitizers, as they exhibit excellent biocompatibility, negative electron affinity that confers a high reactivity with oxygen species (ROS) and an increased induction of DNA DSBs. The characteristics of H-NDs allows electron emission from H-NDs following irradiation by photons and in consequence may enhance the effects of radiation on cancer cells [ 91 , 92 ].…”
Section: Application Of Interaction Of Aunps In Combination With Imentioning
confidence: 99%
“…This year, in an attempt to identify if physical properties are correlated with the survival fraction of cells exposed to low-energy protons in combination with metallic NPs, an interdisciplinary group in Belgium [ 92 ] performed Monte Carlo simulations (based on the latest version of the Geant4 toolkit), assessing also in their study the influence of nanoparticle coating on dose enhancement. They conclude that, although significant efforts will be required to unravel the relevant mechanisms of action, ROS-induced damage and local heating generated from metallic NPs are likely to become fields of importance in radiation therapy research, despite a DNA-centered dogma.…”
Section: Application Of Interaction Of Aunps In Combination With Imentioning
confidence: 99%
“…Because experimental data contradicted initial expectations that high-Z element nanoparticles would perform poorly as radiosensitizers, several computational studies have been performed to understand the mechanism of sensitization. Although different conclusions have been reported depending on the method used, all simulations agreed that radial dose enhancement is localized around the nanoparticle surface, fading after a few nanometers [80][81][82]. Hence, it has been proposed that the physical radiation-based effect is not primarily responsible for an enhanced therapeutic response, and other nanoparticleinduced biological or chemical processes may be involved [81].…”
Section: Protons As Ionizing Radiationmentioning
confidence: 98%